Rancang Bangun Sistem Controlling Rpm Pada Main Engine Berbasis Arduino Uno Guna Mencegah Terjadinya Overspeed - Reski Kurniawan; Agus Dwi Santoso; Upik Widyaningsih (Jurnal Kendali Teknik dan Sains, 2024)
As an important means of sea transportation for the distribution of goods and human mobility between islands, ships require a reliable prime mover to avoid wear or damage, especially when overspeeding occurs which can result in fire. Therefore, a prototype was created that uses an IR Obstacle sensor to monitor the RPM speed of the rotating engine. By using Arduino Uno as a processor, this prototype is able to display the RPM value on the LCD and provide a signal in the form of a green light if the speed is below 4000 Rpm, as well as a red light and buzzer sound if overspeed occurs above 4000 Rpm, followed by the engine turning off after 15 seconds. Testing shows that this prototype has a high level of accuracy, with a difference between 0.08% to 2.73% and an average difference of 1.003%.